The Genetic Engineering of Food and the Failure of Science – Part 2: Academic Capitalism and the Loss of Scientific Integrity - Lotter, Don (The International Journal of Sociology of Agriculture and Food, 2009)
Factors in the failure of the scientific community to properly oversee agricultural transgenics are presented. The large-scale restructuring of university science programs in the past 25 years from a model based on non-proprietary science for the ‘public good’ to the ‘academic capitalism’ model based on the ‘knowledge economy’ is discussed in the context of the failure of the science community to oversee the transition of transgenic crop technology from the research stage to commercialization. Discussed are increasing science community and university dependence on private industry funding and on development of proprietary technologies; monopolization of the make-up of expert scientific bodies on transgenics by pro-industry scientists with vested interests in transgenics; deficient scientific protocols, bias, and possible fraud in industry-sponsored and industry-conducted research; increasing politically and commercially driven manipulation of science within federal regulatory bodies such as the FDA; and bias in the peer-review process, tolerance by the scientific community of biotechnology industry manipulation of the information environment, and of biased treatment and harassment of non-compliant scientists. Discussed are future food production strategies for developing countries, recently framed in the 2008 UNsponsored International Assessment of Agricultural Knowledge, Science, and Technology, an action plan that emphasizes non-proprietary, agroecology-based approaches to food production and does not include crop transgenics as a central strategy. The under-funding of non-proprietary agroecological approaches to food production is discussed.